Fibrin Degradation Products in Normal and Abnormal Pregnancy and Parturition. Issue 5663 (19th July 1969) - Bonnar, John; Davidson, J. F.; Pidgeon, Christine F.; McNicol, G. P.; Douglas, A. S.
Abstract : The levels of fibrin, fibrinogen degradation products (F.D.P.) in the serum were investigated in normal pregnancy and parturition, after caesarean section, and in patients with abruptio placentae, eclampsia, intrauterine death, and post-partum haemorrhage. No significant change occurred during normal pregnancy, but a highly significant increase was found during labour and again during the first week after normal delivery. After caesarean section the levels of F.D.P. were increased two to four hours after operation, and substantially higher levels were found three to eight days after operation than after normal delivery. High levels of F.D.P. were associated with abruptio placentae and eclampsia, and increased levels after intrauterine death and post-partum haemorrhage. An excess of F.D.P. with diminished or normal systemic fibrinolytic activity suggests that local intravascular fibrin deposition and fibrinolysis occur in normal parturition and in these complications of pregnancy. The very high levels of F.D.P. found in abruptio placentae will be important in the pathogenesis of the defective haemostasis that may accompany this complication.